2022
DOI: 10.1136/bmjpo-2022-001417
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents amid emerging COVID-19 pandemic in Bissau, Guinea-Bissau: a qualitative study

Abstract: BackgroundWorldwide, governments have implemented restrictions on movement and gatherings to contain the COVID-19 pandemic. In the spirit of the Convention on the Rights of the Child, children have a right to express their opinion on matters of concern to them. The study aimed to describe and analyse how adolescents in the capital Bissau understood the unfolding COVID-19 pandemic and their lived experiences during the first 3 months of the pandemic.MethodsCollaborators identified participants in five urban are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…During this period, schools were closed, both public and private schools, and it was not clear when schools would be allowed to reopen. At this initial stage of the pandemic, the Bissau-Guinean population generally complied with the lockdown measures, despite its severe impact on daily lives, including those of adolescents [ 40 ]. At the time of the study, the number of confirmed COVID-19 cases was 1614 nationwide, but these were mainly in Bissau (91%), with 21 deaths being reported [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During this period, schools were closed, both public and private schools, and it was not clear when schools would be allowed to reopen. At this initial stage of the pandemic, the Bissau-Guinean population generally complied with the lockdown measures, despite its severe impact on daily lives, including those of adolescents [ 40 ]. At the time of the study, the number of confirmed COVID-19 cases was 1614 nationwide, but these were mainly in Bissau (91%), with 21 deaths being reported [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…The study is one component of a larger research project that aims to articulate and explore manifestations of inequality among Bissau-Guinean adolescents in and out of school [ 10 , 39 , 40 , 46 , 53 , 54 ]. It was approved by the Ethics Committee of the University of Iceland (no: SHV2020-020) and by the Minister of Education in Guinea-Bissau (no/ref 250/MEES/GM/2017), in line with national regulations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] The unfolding COVID-19 pandemic in early 2020 affected children and young people across countries and continents in a myriad of ways. [5][6][7] This early period was critical for many of them as they were experiencing school closures and living in lockdown. The restrictive measures applied by governments made it even more difficult for researchers to reach out to children and young people with rights-based methods designed to engage them as participants to solicit their non-proxied voices to address the impact of COVID-19 on them.…”
Section: Introductionmentioning
confidence: 99%
“…The unfolding COVID‐19 pandemic in early 2020 affected children and young people across countries and continents in a myriad of ways 5‐7 . This early period was critical for many of them as they were experiencing school closures and living in lockdown.…”
Section: Introductionmentioning
confidence: 99%